Brain amyloid in virally suppressed HIV-associated neurocognitive disorder. Issue 4 (July 2020) - Howdle, Gemma C.; Quidé, Yann; Kassem, Mustafa S.; Johnson, Kate; Rae, Caroline D.; Brew, Bruce J.; Cysique, Lucette A.
Abstract : Objective: To determine whether virally suppressed HIV neuropathogenesis, a chronic neuroinflammatory state, promotes abnormal brain amyloid deposition. Methods: A total of 10 men with virally suppressed HIV-associated neurocognitive disorder (HAND), aged 46–68 years, underwent 11 C-labeled Pittsburgh compound B PET. Data from the Australian Imaging, Biomarkers and Lifestyle (AIBL), including 39 cognitively normal individuals (aged 60–74 years), 7 individuals with mild cognitive impairment (MCI) (aged 64–71 years), and 11 individuals with Alzheimer disease (AD) (aged 55–74 years), were used as reference. Apart from more women, the AIBL cohort was demographically comparable with the HIV sample. Also, the AIBL PET data did not differ by sex. Cerebellum standardized uptake value ratio amyloid values within 22 regions of interest were estimated. In the HIV sample, apolipoprotein E (APOE) was available in 80%, CSF biomarkers in 60%, and 8–10 years of long-term health outcomes in 100%. Results: HAND and the AIBL group with no cognitive deficits had similar amyloid deposition, which was lower than that in both the MCI and AD groups. At the individual level, one HAND case showed high amyloid deposition consistent with AD. This case also had a CSF-AD–like profile and an E4/E4 for APOE. Clinically, this case declined over 18 years with mild HAND symptoms first, followed by progressive memory decline 8–9 years after the study PET, then progression to severe dementia within 2–3 years, and lived a further 6 years. Another HAND case showed increased amyloid deposition restricted to the hippocampi. Two other HAND cases showed abnormally decreased amyloid in subcortical areas. Conclusions: Relative to cognitively normal older controls, brain amyloid burden does not differ in virally suppressed HAND at the group level. However, individual analyses show that abnormally high and low amyloid burden occur.